Pengaruh Rasio Semen - Zeolit dan Jumlah Material Stabilisasi Terhadap Sifat Fisik dan Mekanik Tanah Ekspansif - Joice Elfrida Waani; Mecky Richards Emanuel Manoppo; Agnes Tegla Mandagi (Department of Civil Engineering, Diponegoro University, 2025)
Expansive clays is one of the problematic soils which cause numerous problems in pavement engineering and construction such as on airports, highways and roads. Although cement is widely used commonly perceived as the most conventional materials used in treating expansive soils in geotechnical and geoenvironmental engineering applications, of treating expansive soils the increasing trend of cement production has resulted in considerable environmental issues like raising the greenhouse gas emission. The present investigation aims at documenting the effect of adding zeolite a natural pozzolans as a supplementary cementitious material - on the mechanical and physical behaviour of cement stabilized expansive soil mixture. Specifically the Influence of cement-zeolite ratio and level. Soil samples for testing consisted of two different mixtures, namely Clay Soil with 15% bentonite addition and Clay Soil without bentonite addition, each with five binder contents (5%, 7%,10%, 12%, 14%) and various cement to zeolite ratios (5:0; 7:0; 5:5; 7:3; 5:7; 7:5; 5:9; 7:7) were prepared for experimentation. Tests conducted on all soil mixture samples, namely Compaction Test, CBR and UCS revealed that the effectiveness of adding zeolite on the strength of expansive clay soil mixtures is at cement-zeolite percentages of 10%; 12% and 14%, at all cement-zeolite ratios.